2020
DOI: 10.1111/eje.12585
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between Facebook behaviour and e‐professionalism: A questionnaire‐based cross‐sectional study among Greek dental students

Abstract: Introduction The social media attitude of health science students might affect patients' opinion about the health profession and have negative impact on e‐professionalism. The aim of this study is to investigate the behaviour of Greek dental students on Facebook, focusing on potentially unprofessional posts and the online student‐patient relationship. Materials and methods Five hundred and twelve dental students in Greece answered an anonymous, 23‐item questionnaire including multiple‐choice questions about va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 41 publications
1
31
0
Order By: Relevance
“…Among 88 studies, 49 were quantitative [ 32 , 33 , 35 , 38 - 43 , 51 - 53 , 55 , 59 - 61 , 64 , 66 - 69 , 71 , 72 , 74 , 75 , 77 - 80 , 82 , 85 , 88 , 89 , 91 , 94 - 96 , 98 , 100 , 102 , 105 - 108 , 110 , 113 , 114 , 116 , 118 ], 12 were qualitative [ 34 , 36 , 44 , 45 , 49 , 57 , 73 , 76 , 92 , 93 , 101 , 104 ], and 27 used mixed methods [ 35 , 37 , 46 - 48 , 50 , 54 , 56 , 58 , 62 , 63 , 65 , 70 , 81 , 83 , 84 , 86 , 87 , 90 , 97 , 99 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among 88 studies, 49 were quantitative [ 32 , 33 , 35 , 38 - 43 , 51 - 53 , 55 , 59 - 61 , 64 , 66 - 69 , 71 , 72 , 74 , 75 , 77 - 80 , 82 , 85 , 88 , 89 , 91 , 94 - 96 , 98 , 100 , 102 , 105 - 108 , 110 , 113 , 114 , 116 , 118 ], 12 were qualitative [ 34 , 36 , 44 , 45 , 49 , 57 , 73 , 76 , 92 , 93 , 101 , 104 ], and 27 used mixed methods [ 35 , 37 , 46 - 48 , 50 , 54 , 56 , 58 , 62 , 63 , 65 , 70 , 81 , 83 , 84 , 86 , 87 , 90 , 97 , 99 , …”
Section: Resultsmentioning
confidence: 99%
“…Studies that assessed SM use among different types of HCPs found high use among students, from 66.9% to 98.7% [ 40 , 43 , 50 , 51 , 60 , 61 , 64 - 66 , 68 - 70 , 102 ]; the highest with 98.7% using Facebook at least once a week was established among dental students. Lower rates of use were seen in practicing HCPs, physicians of different specialties, and program directors (PDs) or faculty, mostly ranging from 50% to 80% [ 35 , 39 , 74 , 80 , 83 , 85 , 86 , 88 , 89 , 91 , 96 , 105 , 106 , 108 , 110 , 113 , 114 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These issues were also found in previous studies. [ 3 11 , 17 18 ] However, the percentage of these accounts was not quite high, and the students were likely to share patient information with positive purposes, such as to share knowledge or to get comments about their works. The clearly unprofessional content to be concerned was “Parody content of patients” and “Complaint about patients,” which could negatively affect perceptions of patients toward dental students.…”
Section: Discussionmentioning
confidence: 99%
“…However, this problem was likely to be the common unprofessionalism in other researches. [ 3 4 , 8 9 , 18 21 ] As alcohol consumption was considered as a health-destructive behavior and healthcare professionals were expected to be a role model,[ 19 ] posts of students drinking alcohol would negatively affect their images and therefore it was considered as unprofessionalism.…”
Section: Discussionmentioning
confidence: 99%